2019
DOI: 10.1002/bsl.2440
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of people with mental health problems at hot spots: Attitudes and perceptions of safety, crime, and the police

Abstract: People who live in places with high levels of crime and disorder are more likely to experience mental illness compared with those who do not live in these types of place (Weisburd et al., 2018; Weisburd & White, 2019). The increased police presence on high crime streets may also increase the likelihood that these individuals will encounter law enforcement. There is a strong body of literature focused on the relationship between neighborhoods and the physical and mental health of residents (e.g. Arcaya et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Finally, a strength of this study was its use of reported crime data geocoded to the street address which enabled the assignment of crimes to individual buffers rather than the adoption of administrative boundaries. The finding reported at the 1 km network buffer scale support the limited evidence available that has found associations with increased specificity of measurement of crime exposure beyond the aggregation of administrative boundaries ( Goldberg, White & Weisburd, 2019 ; Weisburd et al, 2018 ). In Australian and other jurisdictions, more authorities should consider making geocoded crime data available for research purposes to enable spatial relationships with mental health outcomes to be uncovered.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, a strength of this study was its use of reported crime data geocoded to the street address which enabled the assignment of crimes to individual buffers rather than the adoption of administrative boundaries. The finding reported at the 1 km network buffer scale support the limited evidence available that has found associations with increased specificity of measurement of crime exposure beyond the aggregation of administrative boundaries ( Goldberg, White & Weisburd, 2019 ; Weisburd et al, 2018 ). In Australian and other jurisdictions, more authorities should consider making geocoded crime data available for research purposes to enable spatial relationships with mental health outcomes to be uncovered.…”
Section: Discussionsupporting
confidence: 77%
“…Law enforcement officers, without specialized medical training, often find themselves in situations involving individuals with mental illness. These encounters result from the fact that officers are frequently the first responders to crises involving mental illness (Goldberg et al 2019). Despite department-regulated training, it is clear that officers are not fully equipped to handle the complexities of mental illness, hence the moniker "street corner psychiatrists."…”
Section: How Law Enforcement Officers Assess Mental Illnessmentioning
confidence: 99%
“…Wittmann et al ( 2020 ) found that police encounters were chiefly experienced as positive, respectful, and non-threatening. Other recent research indicates that people with mental illness view police experiences as decidedly negative (Goldberg et al 2019 ; van der Meulen et al 2021 ), which can hinder future help-seeking, trust in police, and perceptions of police legitimacy. Relatedly, families report fear in calling police for assistance during a loved one’s mental health crisis and cite concerns about excessive use of force and lack of police training in responding to mental health crisis (Baker and Pillinger 2020 ; Lavoie 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%